The TRPA1 ion channel is expressed in CD4+ T cells and restrains T-cell-mediated colitis through inhibition of TRPV1. Issue 9 (20th June 2016) - Bertin, Samuel; Aoki-Nonaka, Yukari; Lee, Jihyung; de Jong, Petrus R; Kim, Peter; Han, Tiffany; Yu, Timothy; To, Keith; Takahashi, Naoki; Boland, Brigid S; Chang, John T; Ho, Samuel B; et al.
Abstract : Objective: Transient receptor potential ankyrin-1 (TRPA1) and transient receptor potential vanilloid-1 (TRPV1) are calcium (Ca 2+ )-permeable ion channels mostly known as pain receptors in sensory neurons. However, growing evidence suggests their crucial involvement in the pathogenesis of IBD. We explored the possible contribution of TRPA1 and TRPV1 to T-cell-mediated colitis. Design: We evaluated the role of Trpa1 gene deletion in two models of experimental colitis (ie, interleukin-10 knockout and T-cell-adoptive transfer models). We performed electrophysiological and Ca 2+ imaging studies to analyse TRPA1 and TRPV1 functions in CD4+ T cells. We used genetic and pharmacological approaches to evaluate TRPV1 contribution to the phenotype of Trpa1 −/− CD4+ T cells. We also analysed TRPA1 and TRPV1 gene expression and TRPA1 + TRPV1 + T cell infiltration in colonic biopsies from patients with IBD. Results: We identified a protective role for TRPA1 in T-cell-mediated colitis. We demonstrated the functional expression of TRPA1 on the plasma membrane of CD4+ T cells and identified that Trpa1 −/− CD4+ T cells have increased T-cell receptor-induced Ca 2+ influx, activation profile and differentiation into Th1-effector cells. This phenotype was abrogated upon genetic deletion or pharmacological inhibition of the TRPV1 channel in mouse and human CD4+ T cells. Finally, we found differential regulation of TRPA1 and TRPV1 gene expression as well as increased infiltration of TRPA1 + TRPV1 + T cells in the colon of patients with IBD. Conclusions: Our study indicates that TRPA1 inhibits TRPV1 channel activity in CD4+ T cells, and consequently restrains CD4+ T-cell activation and colitogenic responses. These findings may therefore have therapeutic implications for human IBD.